Impact of Obesity on Vaccination to SARS-CoV-2 - Nasr, Michaella-Jana C.; Geerling, Elizabeth; Pinto, Amelia K. (Frontiers in Endocrinology, 2022)
To combat the immense toll on global public health induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), new vaccines were developed. While these vaccines have protected the populations who received them from severe SARS-CoV-2 infection, the effectiveness and durability of these vaccines in obese individuals is not fully understood. Our uncertainty of the ability of these novel vaccines to induce protective immunity in obese humans stems from historical data that revealed immune defects to influenza vaccines in obese patients. This review analyzes the efficacy of SARS-CoV-2 vaccines in the obese population. According to the vaccine safety and efficacy information for the Pfizer, Moderna, and Johnson & Johnson formulations, these vaccines showed a similar efficacy in the obese and healthy weight populations. However, clinical trials that assess BMI and central obesity showed that the antibody titer are lower in obese individuals when compared to healthy weight subjects. Thus, the desired protective effects of the SARS-CoV-2 vaccination were diminished in the obese population when compared to the healthy weight population. Additional research must be completed to truly understand the immune responses mounted against this specific respiratory virus in obese patients, and whether these responses differ from those elicited by previously studied influenza viruses.